The Relationship Between Academic Stress And Eyestrain In High School - Ni Putu Puspita Dewi; Ni Kadek Muliawati; Putu Gede Subhaktiyasa (Journal Nursing Research Publication Media (NURSEPEDIA), 2026)
Background: Academic stress is a psychological problem that adolescents often experience and has the potential to cause physical disorders, including eyestrain, especially in digital device-based learning. Objective: This study aims to analyze the relationship between academic stress and eyestrain in adolescents at Public Senior High School Negeri 2 Sukawati. Methods: The research design is cross-sectional. The population amounted to 338 students. The sampling technique used proportionate stratified random sampling, and the sample consisted of 183 respondents among first- and second-grade students. Academic stress was measured using the Educational Stress Scale for Adolescents (ESSA) questionnaire, and eyestrain was measured by the Visual Fatigue Index (VFI) questionnaire. Data analysis used the Chi-Square test with a significance level of 0.05. Results: The dominant level of academic stress was the moderate category (66.1%), and most respondents experienced eyestrain (81.4%). Statistical tests showed a significant association between academic stress and eyestrain (p = 0.002). Conclusion: Academic stress increases the risk of eyestrain in adolescents. These findings emphasize the importance of efforts to manage academic stress and control the use of digital devices as part of adolescent health promotion in the school environment.